Patellariopsidaceae Fam. Nov. With Sexual-Asexual Connection and a New Host Record for Cheirospora botryospora (Vibrisseaceae, Ascomycota) - Karunarathna, Anuruddha; Peršoh, Derek; Ekanayaka, Anusha H.; Jayawardena, Ruvishika S.; Chethana, K. W. Thilini; Goonasekara, Ishani D.; Cheewangkoon, Ratchadawan; Camporesi, Erio; Hyde, Kevin D.; Lumyong, Saisamorn; Karunarathna, Samantha C. (Frontiers in Microbiology, 2020)
Helotiales is a polyphyletic order of Ascomycetes. The paucity of relevant molecular data and unclear connections of sexual and asexual morphs present challenges in resolving taxa within this order. In the present study, Patellariopsidaceae fam. nov., the asexual morph of Patellariopsis atrovinosa, and a new record of Cheirospora botryospora (Vibrissiaceae) on Fagus sylvatica (Fagaceae) from Italy are discussed based on morphology and molecular phylogeny. Phylogenetic analyses based on sequence data of combined LSU and ITS were used to improve the phylogenetic resolution in the polyphyletic Helotiales. The results of this research have paved a solid base to the taxonomy and phylogeny of Helotiales.